Evaluating the role of black rice husk ash nanoparticles in enhancing foam stability for enhanced oil recovery - Ahmad, Ishaq; Zhao, Wanchun; Wang, Tingting; Khan, Javed Akbar; Irawan, Sonny (Frontiers in Chemical Engineering, 2026)
IntroductionFoams have been considered for their ability to control in solution, gas injection improved oil recovery (IOR) processes, for blocking and diverting using either gelled foams, and for gas and oil ratio control at production wells. In a range of applications, a foam meets a range of oil saturations, which requires the design of a foam with the necessary stability for oil saturation. The stability of foams in oil is extremely important for the oil industry. Core flood experiments by different investigators suggest that oil becomes harmful to foam at oil saturation levels above 5% to 20%. The use of such foams is notably advantageous over the use of simple fluids with similar nominal mobility because of the foam and with a viscosity higher than that of the displaced fluids. This is because surfactant-stabilized foams reduce the mobility of the gas present in the higher permeability portions. This causes a diversion of the displacing gas to the formation parts that were previously unswept. Additional oil can be recovered from underswept areas.MethodsThe black rice husk ash used in this study was sourced from a Japanese rice husk ash company. The anionic foaming surfactant, Sodium Dodecyl Benzene Sulfonate (SDBS), was obtained from Sigma. The experimental setup included two 1.5-liter cylinders for the mixed solution and one cylinder for CO. A sand pack measuring 30 cm in length and 2.5 cm in radius was used, and the sand and black rice husk ash were sieved using a 0.125 mm sieve. It was then filled with local white sand particles of 0.0125 mm. The high-pressure pump employed for the fluid pressure was a 100DX syringe pump capable of operating at pressures of up to 10,000 psi (690 bar).Results0.5 wt. % concentration of rice husk ash and SDBS surfactant was mixed with 1000 mL of water. The mixture was stirred on a magnetic stir plate for over 20 min. The experimental setup is illustrated The experiment conducted without a sand pack and with a sand pack. Pressure pumps were connected to a CO2 gas cylinder and a mixed solution of rice husk ash and SDBS surfactant via a connector, which also included a flow meter to monitor the flow rate. Foam generators were attached to produce foam for the experiment. Pressure meter was attached via a large connector to monitor the pressure during the experiment. The sand pack experimental design offers valuable insights into the foam lifespan and stability under sand pack conditions relevant to EOR. An oil field firm (Dongying, China) provided the oil. Oil was extracted from the unconsolidated sandstone reservoir of the oilfield. The oil viscosity of the black rice husk ash and SDBS surfactant was 40 mPa. Three core flood and three foam-flooding experiments were conducted to obtain the best results. The first experiment failed because of the leakage of gas at the connecting point, which was difficult to detect. After completing the sand pack experiments, the foaming mechanism was investigated further.DiscussionFoam volume and sand pack influence: without a sand pack, the initial foam volume of black rice husk ash foam is relatively high. However, in the presence of a sand pack, the volume decreases. Adding black rice husk ash liquid at a modest concentration can optimize foam volume across various temperatures. The foam drainage half-life is significantly influenced by incorporating black rice husk ash at different liquid flow rates. Viscosity and bubble stability: The addition of black rice husk ash foaming agents to oil reduces its viscosity. Despite a significant increase in bubble velocity, the stability of the bubbles decreases. However, these tiny foam bubbles exhibit longer stability compared to the initial phase. Foam stability in sand pack conditions: In sand pack conditions, black rice husk ash positively impacts foam stability and strength both before and after flooding. However, the foam lifetime becomes limited after sand pack flooding. Oil recovery enhancement: Injecting black rice husk ash foam into a sand pack increases oil recovery. Microscopic studies and recovery points indicate that the silica nanoparticles in black rice husk ash contribute significantly to foam ability and stability.